Suicide literacy among first year undergraduate healthcare students in Universiti Sains Malaysia - Sahar, Siti Ainul Farhana (2021)
Suicide has become a formidable challenge to the mental health practice as the warning signs could manifest subtly or they could be instantaneous. Suicide literacy is a recognised approach to prevent suicide, which involves improving the identification and treatment of individuals at high risk. This study aims to examine the level of suicide literacy among first year healthcare student in Universiti Sains Malaysia (USM) and its predictors.